2023
DOI: 10.3390/mi14081589
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible High-Resolution 3D-Printed Microfluidic Devices: Integrated Cell Chemotaxis Demonstration

Abstract: We demonstrate a method to effectively 3D print microfluidic devices with high-resolution features using a biocompatible resin based on avobenzone as the UV absorber. Our method relies on spectrally shaping the 3D printer source spectrum so that it is fully overlapped by avobenzone’s absorption spectrum. Complete overlap is essential to effectively limit the optical penetration depth, which is required to achieve high out-of-plane resolution. We demonstrate the high resolution in practice by 3D printing 15 μm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Membranes with various pore sizes were designed and printed on a custom 3D printer reported in ref. 10 and 17 which is based on a DMD with 7.6 μm pixels and uses 1 : 1 projection optics, yielding square 7.6 μm pixels in the image plane. We used a custom photopolymerizable resin consisting of poly(ethylene glycol) diacrylate (PEGDA, MW258) with a 1% (w/w) phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Irgacure 819) photoinitiator and a 0.38% (w/w) Avobenzone UV absorber, the same resin reported in ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Membranes with various pore sizes were designed and printed on a custom 3D printer reported in ref. 10 and 17 which is based on a DMD with 7.6 μm pixels and uses 1 : 1 projection optics, yielding square 7.6 μm pixels in the image plane. We used a custom photopolymerizable resin consisting of poly(ethylene glycol) diacrylate (PEGDA, MW258) with a 1% (w/w) phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Irgacure 819) photoinitiator and a 0.38% (w/w) Avobenzone UV absorber, the same resin reported in ref.…”
Section: Methodsmentioning
confidence: 99%
“…We used a custom photopolymerizable resin consisting of poly(ethylene glycol) diacrylate (PEGDA, MW258) with a 1% (w/w) phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Irgacure 819) photoinitiator and a 0.38% (w/w) Avobenzone UV absorber, the same resin reported in ref. 9 and 10. The devices were printed on 25 mm square silanized glass substrates, prepared as described in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution (10-15 μm) features have been developed by DLP-SLA technology for biomedical applications such as micropillars, valves, pumps and microchannels. Utilising the absorption range of the biocompatible resin Avobenzone, Boaks et al 95 demonstrated cellular migration through their lab-on-chip device (Figure 13A). Enclosed serpentine microchannels have been fabricated through DLP-SLA by Tzivelekis et al 94 to carry out two-step polymerase chain reaction (PCR) thermocycling.…”
Section: Microfluidic Devices Fabricated Through Dlp-sla Technologymentioning
confidence: 99%
“…DLP-SLA printed microfluidic chip developed for (A) cellular migration and (B) two-step PCR thermocycling set-up. (a) Open microchannel geometry with a serpentine pattern, (b) 3D model assembly of PCR chip, (c) Schematic of the two-step PCR thermocycling, (d) Peltier pairs for thermocycling setup and (e) PCR sample pressurisation.Source: (A) Ref 95. ; (B) reprinted with permission94 Copyright © 2021 IOP Publishing Ltd.…”
mentioning
confidence: 99%